Kumbang pemakan daun palem Pelagodoxa henryana Becc. di Kebun Raya Bogor, Indonesia - Nadzirum Mubin; Fitri Fatma Wardani; Rizmoon Nurul Zulkarnaen; Inggit Puji Astuti; Joko Ridho Witono (Jurnal Entomologi Indonesia, 2022)
Bogor Botanical Garden (BBG) is a conservation site with various type of collections such as threatened palm species, including Pelagodoxa henryana Becc. which has been categorized as critically endangered species. During its development, some of the plants did not grow optimal due to insect pests attack. The purpose of the study was to identify insect pest species that attack the P. henryana in BBG. The method used was observation with purposive sampling on eight palms P. henryana in BBG then insects were collected and identified. The results showed that insect pest attacked young leaf and also unopened leaf. The insects hide between the leaves, causing young leaves became dry up then died. Based on species identification, two leaf beetles were found i.e., Brontispa longissima (Gestro) and Wallacea sp. (Coleoptera: Chrysomellidae).